Influence of an Educational Intervention on Eating Habits in School-Aged Children - María José Menor-Rodriguez; Jonathan Cortés-Martín; Raquel Rodríguez-Blanque; María Isabel Tovar-Gálvez; María José Aguilar-Cordero; Juan Carlos Sánchez-García (MDPI AG, 2022)
A health promotion intervention directed at preventing unhealthy habits in relation to physical exercise, hygiene habits, diet and personal relationships can lead to a decrease in diseases during adulthood and obtaining a better quality of life. The intervention had a participative and multidisciplinary nature, and it was developed by health professionals, teachers and parents for school children. It promoted healthy lifestyle habits around food by working on four areas through video lessons, interactive talks, practical and theoretical-practical classes and an individual project on behalf of the student where they had to design healthy menus. We randomly selected, by stratified multistage sampling, three public primary education schools. A sample of 479 students registered during the 2014/2015 academic year aged between 6-12 years were included in the study. After the educational intervention, we found a significant reduction in the BMI of the students (p < 0.001). For breakfast, the overweight or obese children modified their usual food consumption after the intervention for a healthier breakfast based on fruit juice and bread instead of sugary snacks (p < 0.001). Regarding eating habits during the mid-morning break, there was a decrease in the consumption of sugary snacks (p < 0.001) and an increase in the consumption of fruits and sandwiches. We found that, after the intervention, the excessive consumption of pasta for the main meal reduced in favor of an increase in the consumption of proteins and different beans and pulses (p > 0.001). Educational interventions on healthy lifestyle habits carried out in children during their early years improve and correct unhealthy habits.